A DUAL PERSPECTIVE: TEACHERS AND STUDENTS' PERCEPTIONS OF AUGMENTED REALITY FLASHCARDS APP - Astawa, Ni Luh Putu Ning Septyarini Putri (Yavana Bhasha : Journal of English Language Education, 2025)
This qualitative case study investigated the perceptions of teachers and students regarding the implementation of an Augmented Reality (AR) flashcard application namely “Fruit Troduction” in a fourth-grade classroom in Denpasar, Bali. Through questionnaires and interviews with 22 EFL students and two teachers, the study sought to understand how the teachers and students perceived learning that integrates AR technology into elementary education. Data analysis revealed positive responses from both teachers and students, highlighting the AR app's effectiveness in enhancing engagement, motivation, and learning outcomes. The findings suggest that AR technology holds significant promise for transforming traditional teaching methods and fostering a more immersive and interactive learning environment in elementary classrooms.